ON STRONGLY PRIME SUBMODULES - Naoum, A.; Hadi, I. (Iraqi Journal of Science, 2025)
Let R be an integral domain with quotient field K. A prime ideal P of R is calleda strongly prime ideal of R if for each x, y ∈ K, x y ∈ P implies x ∈ P or y ∈ P. Inthis paper, we generalize this concept to submodules, thus we define strongly primesubmodules and give some of their properties.